Feeding levels during early gestation in a group-housing system for primiparous sows: impact on piglet birthweight and litter uniformity - Natchanon Dumniem; Thomas D. Parsons; Padet Tummaruk (Animal Bioscience)
Objective The current study investigated the impacts of different feeding regimes during early gestation on conception rate, litter traits, piglet birthweight, and litter uniformity in primiparous sows. Methods In total, 108 primiparous sows were inseminated and assigned to either a standard (1.9±0.5 kg/d, S) or high (2.9±0.8 kg/d, H) feeding levels during the first 35 days of gestation. The feeding regimes were categorized based on periods of gestation: 1 to 3, 4 to 15, and 16 to 35 days, resulting in four groups: standard-standard-standard (SSS, n = 26), standard-standard-high (SSH, n = 28), standard-high-high (SHH, n = 28), and high-high-high (HHH, n = 26). Afterwards, sows were placed into a group-housed system equipped with electronic sow feeders. The sows were weighed and assessed for backfat thickness and loin muscle depth at 0 and 35 days of gestation. At farrowing, data were collected on the total number of piglets born per litter, piglet birthweights, and the coefficient of variation of piglet birthweights. Results On average, sows gained 22.5±21.6 kg during the first 35 days of gestation, showing a positive correlation with backfat gain (r = 0.954; p = 0.006). The backfat gain in the HHH group was higher than in the SSS (p = 0.016) and the SSH groups (p = 0.023), but did not differ from the SHH group (p = 0.684). Conception rates did not show differences among the feeding regimes (p>0.05). Individual piglet birthweights in the HHH group were higher than those in the SSH group (p<0.001). Likewise, the percentage of piglets with birthweights <1,000 g in the HHH group was lower than that in the SSH group (p<0.001). However, the variation of piglet birthweight did not differ among the groups (p>0.05). Conclusion Increasing feeding levels in primiparous sows in a group-housed system during early pregnancy can effectively restore their body condition without any detrimental effects on subsequent litters.